(untitled) (Web of Teachers: Inderscience Research, 2023)
This study aimed at identifying various ways and techniques during teaching listening to the beginners. Nowadays, most of the learners are facing with difficulties about understanding listening audio and podcasts. There are many methods identified by experts. The importance of contextualized activities, pre-listening activities, comprehension strategies, authentic listening materials, and visual support will be discussed. These strategies, supported by recent research findings, offer valuable insights for language educators seeking innovative and effective teaching techniques proficiency among beginner level students.